Cyclin D1 Stability Is Partly Controlled by O-GlcNAcylation - Masclef, Louis; Dehennaut, Vanessa; Mortuaire, Marlène; Schulz, Céline; Leturcq, Maïté; Lefebvre, Tony; Vercoutter-Edouart, Anne-Sophie (Frontiers in Endocrinology, 2019)
Cyclin D1 is the regulatory partner of the cyclin-dependent kinases (CDKs) CDK4 or CDK6. Once associated and activated, the cyclin D1/CDK complexes drive the cell cycle entry and G1 phase progression in response to extracellular signals. To ensure their timely and accurate activation during cell cycle progression, cyclin D1 turn-over is finely controlled by phosphorylation and ubiquitination. Here we show that the dynamic and reversible O-linked -N-Acetyl-glucosaminylation (O-GlcNAcylation) regulates also cyclin D1 half-life. High O-GlcNAc levels increase the stability of cyclin D1, while reduction of O-GlcNAcylation strongly decreases it. Moreover, elevation of O-GlcNAc levels through O-GlcNAcase (OGA) inhibition significantly slows down the ubiquitination of cyclin D1. Finally, biochemical and cell imaging experiments in human cancer cells reveal that the O-GlcNAc transferase (OGT) binds to and glycosylates cyclin D1. We conclude that O-GlcNAcylation promotes the stability of cyclin D1 through modulating its ubiquitination.